Implementasi Model Penilaian Proyek Dalam Pembelajaran Matematika Berbasis Lesson Study Di Smp Muhammadiyah 1 Kartasura(Pada Siswa Kelas VII Semester Genap Tahun 2015/2016) - Yuli Puji Astuti, Riska, Dr. Sumardi, M.Si (2016)
Abstract The purpose of this study was to (1) The use of project appraisal already understand teacher at SMP Muhammadiyah 1 Kartasura, (2) Describe the implementation of the project assessment based on learning lesson study, (3) Describe the obstacles in the application of learning the lesson study with the assessment of the project. The study was conducted in classes VIIB SMP Muhammadiyah 1 Kartasura totaling 34 people composed of 12 female students and 22 male students. This research is qualitative descriptive. Data collection techniques used include interviews, field notes, documentation. Data analysis techniques used in the study that recorded the results of field notes, collect data, and gives meaning to the data obtained. It can be concluded that (1) The understand teacher of project evaluation form about the pre-test, EHS, and post-test to determine the ability of students to understand the material, gathering information, identifying information, and concluded as well as inform the front of the class is given in stages. (2) The implementation of the project assessment in which is based on learning the lesson study is to apply the stages pland, do, see at every meeting affect the performance of teachers at the first meeting of 40%, second 60%, third 70%, and the fourth 90%, the percentage of questions and answers and the average pre-test and post-test students' first meeting 30%, 35.27 and 41.33, the second 50%, 45.82 and 53.55, the third 60%, 53.15 and 60.18, and The fourth meeting of 80%, 73.83 and 79.06. (3) The problem faced is damaged LCD, feeling lazy student, initially learning to do, and time is limited. Keywords: judging project, lesson study, learning mathematics.